2010
DOI: 10.1183/09031936.00123410
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of lung cancer computed tomography screening on health-related quality of life: the NELSON trial

Abstract: The long-term effects of lung cancer computed tomography (CT) screening on health-related quality of life (HRQoL) have not yet been investigated.In the Dutch-Belgian Randomised Lung Cancer Screening Trial (NELSON trial), 1,466 participants received questionnaires before randomisation (T0), 2 months after baseline screening (screen group only; T1) and at 2-yr follow-up (T2). HRQoL was measured as generic HRQoL (12-item shortform questionnaire and EuroQoL questionnaire), anxiety (Spielberger State-Trait Anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 22 publications
4
87
0
5
Order By: Relevance
“…Lung cancer screening results in incidental findings, some of which lead to further investigations, resulting in moderate additional costs of €8.95 [U.S. $12.67] per patient at baseline and €2.25 [U.S. $3.19] at 5-year follow-up [38]. Another point of discussion is the influence of indeterminate baseline screening results on the quality of life of the patients during lung cancer screening [39]. False positive nodules led to biopsy in 1.2% of the patients who were not found to have lung cancer in both the NLST and the NELSON trial [36].…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer screening results in incidental findings, some of which lead to further investigations, resulting in moderate additional costs of €8.95 [U.S. $12.67] per patient at baseline and €2.25 [U.S. $3.19] at 5-year follow-up [38]. Another point of discussion is the influence of indeterminate baseline screening results on the quality of life of the patients during lung cancer screening [39]. False positive nodules led to biopsy in 1.2% of the patients who were not found to have lung cancer in both the NLST and the NELSON trial [36].…”
Section: Discussionmentioning
confidence: 99%
“…Silvestri et al 92 reported that smokers perceived fewer benefits and were less likely to consider lung cancer screening than non-smokers. Non-participants in NELSON 88 were more likely to be female and former smokers, and to have a lower perceived risk of lung cancer and less-positive beliefs about the benefits of lung screening than participants. 93 In the first 88,897 individuals approached to take part in UKLS, participation was more likely in ex-smokers and those in higher socioeconomic groups.…”
Section: Barriers To Uptake Of Lung Cancer Screeningmentioning
confidence: 92%
“…83,84 The psychosocial impact of LDCT screening for lung cancer has been examined in controlled trials outside the UK, in terms of effects of both trial allocation and screening results. [85][86][87][88][89][90][91] Overall, evidence from these trials suggests that LDCT screening does not produce long-term anxiety or other adverse effects that could deter high-risk individuals from further help-seeking or future participation in a lung screening programme. However, it is important to examine psychosocial effects within the UKLS context to ensure that any future lung screening programme is tailored to the specific needs of the UK high-risk population.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…No long-term psychological harm was found in the NELSON trial. In those with negative results, anxiety and distress fell from baseline; following an abnormal result, anxiety and distress were transient and tended to have returned to baseline by the next screening round [28]. However, the harms-psychological, physical and financial-suffered by those with overdiagnosed tumours have not been quantified and are likely to be substantial.…”
Section: Downsides Of Ldct Screeningmentioning
confidence: 99%